A narrative review on obstructive sleep apnoea syndrome in paediatric population - Vaienti, Benedetta; Di Blasio, Marco; Arcidiacono, Luisa; Santagostini, Antonio; Di Blasio, Alberto; Segù, Marzia (Frontiers in Neurology, 2024)
Obstructive sleep apnoea syndrome is a respiratory sleep disorder that affects 1–5% of children. It occurs equally in males and females, with higher incidence in school age and adolescence. OSAS may be caused by several factors, but in children, adenotonsillar hypertrophy, obesity, and maxillo-mandibular deficits are the most common. In general, there is a reduction in the diameter of the airway with reduced airflow. This condition worsens during sleep due to the muscular hypotonia, resulting in apnoeas or hypoventilation. While snoring is the primary symptom, OSAS-related manifestations have a wide spectrum. Some of these symptoms relate to the nocturnal phase, including disturbed sleep, frequent changes of position, apnoeas and oral respiration. Other symptoms concern the daytime hours, such as drowsiness, irritability, inattention, difficulties with learning and memorisation, and poor school performance, especially in patient suffering from overlapping syndromes (e.g., Down syndrome). In some cases, the child’s general growth may also be affected. Early diagnosis of this condition is crucial in limiting associated symptoms that can significantly impact a paediatric patient’s quality of life, with the potential for the condition to persist into adulthood. Diagnosis involves evaluating several aspects, beginning with a comprehensive anamnesis that includes specific questionnaires, followed by an objective examination. This is followed by instrumental diagnosis, for which polysomnography is considered the gold standard, assessing several parameters, including the apnoea-hypopnoea index (AHI) and oxygen saturation. However, it is not the sole tool for assessing the characteristics of this condition. Other possibilities, such as night-time video recording, nocturnal oximetry, can be chosen when polysomnography is not available and even tested at home, even though with a lower diagnostic accuracy. The treatment of OSAS varies depending on the cause. In children, the most frequent therapies are adenotonsillectomy or orthodontic therapies, specifically maxillary expansion.